2018
DOI: 10.1002/jcsm.12337
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different palliative systemic treatments on skeletal muscle mass in metastatic colorectal cancer patients

Abstract: BackgroundObservational studies suggest that loss of skeletal muscle mass (SMM) is associated with chemotherapy‐related toxicity, poor quality of life, and poor survival in metastatic colorectal cancer (mCRC) patients. Little is known about the evolution of SMM during palliative systemic therapy. We investigated changes in SMM during various consecutive palliative systemic treatment regimens using repeated abdominal computed tomography scans of mCRC patients who participated in the randomized phase 3 CAIRO3 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 35 publications
(78 reference statements)
2
58
1
2
Order By: Relevance
“…Muscle mass preservation during later stages of advanced cancer, after (extensive) weight loss has occurred, is difficult as the progressive metabolic derangements that occur during cancer (cachexia) may no longer be reversible, at least not by the conventional interventions such as nutritional support . However, there might be a window of opportunity in the initial phase of metastatic disease, as during this phase, patients may still have exploitable anabolic potential . Indeed, in CAIRO3, we observed that muscle loss that occurred during initial 6 cycles CAPOX‐B treatment was reversible during subsequent less intensive CAP‐B treatment or observation .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Muscle mass preservation during later stages of advanced cancer, after (extensive) weight loss has occurred, is difficult as the progressive metabolic derangements that occur during cancer (cachexia) may no longer be reversible, at least not by the conventional interventions such as nutritional support . However, there might be a window of opportunity in the initial phase of metastatic disease, as during this phase, patients may still have exploitable anabolic potential . Indeed, in CAIRO3, we observed that muscle loss that occurred during initial 6 cycles CAPOX‐B treatment was reversible during subsequent less intensive CAP‐B treatment or observation .…”
Section: Discussionmentioning
confidence: 90%
“…Detailed information on muscle mass and body weight changes during CAIRO3 treatments were reported elsewhere . In short, during CAP‐B, 28% of patients lost >2% SMI, and 66% of patients lost >2% SMI during CAPOX‐B.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations